Development of Stability Indicating RP-HPLC Method for Ertapenem in Bulk Drug and Pharmaceutical Dosage Form - Jain, Ruchi; Jain, Nilesh; Jain, Deepak Kumar; Singh, Avineesh; Jain, Surendra Kumar (Dhaka University Journal of Pharmaceutical Sciences, 2017)
A simple, inexpensive, rapid and novel stability indicating isocratic HPLC method has been developed and validated for quantitative analysis of ertapenem sodium in the bulk drug and in pharmaceutical dosage form. An isocratic separation of ertapenem sodium was achieved on Hypersil BDS C18 column (4.6 x 250 mm, 5 ? particle size) as the stationary phase with a flow rate of 1.2 ml/min and using a UV detector to monitor the eluate at 298 nm. The mobile phase consisted of acetonitrile : water (60:40v/v) and pH adjusted 2.9 by othophosphoric acid enabled separation of the drug from its degradation products. The method was validated for linearity, accuracy (recovery), precision, specificity and robustness. The linearity of the method was satisfactory over the range 2-10 ?g/ml (correlation coefficient 0.999). Recovery of ertapenem sodium from the pharmaceutical dosage form ranged from 99.97 to 103.7%. Ertapenem sodium was subjected to stress conditions [hydrolysis (acid, base), oxidation, photolysis and thermal degradation] and the samples were analyzed by this method. The forceddegradation study with ertapenem sodium showed that it was degraded under basic condition. The drug was stable under the other stress conditions investigated. Ertapenem sodium was found to be less stable in solution state, whereas it was comparatively much stable in solid state. The degradation products were well resolved from main peak. The forced degradation study prove the stability indicating power of the method and therefore, the validated method may be useful for routine analysis of ertapenem sodium as bulk drug, in respective dosage forms, for dissolution studies and as stability indicating assay method in pharmaceutical laboratories and industries. Dhaka Univ. J. Pharm. Sci. 16(1): 21-28, 2017 (June)